PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT KUBIK MADANI - Nuridin; Intan Pratiwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
This study was done to determine the influence of partially and simultaneously between working environment and motivation to employee’s performance at PT. Kubic Madani. Method was used for data collection was through primary data. Methods of data analysis with using regression, correlation, determination either jointly or individually, then continued hypothesis testing. The results showed that: From analysis result, regarding the factors were affecting employee’s performance, appears that between two variables were analyzed, work environment and motivation, then the most dominant influence on employee’s performance was variable of work environment. That was proved by the result of calculation of t count each variable, where t count of work environment (10.513) is bigger than the value of t count of motivation (10.183)